Descobrindo o número PI - Keller, Flávia Adolf Lutz (Universidade Federal de São Carlos, 2013)
The value of the circumference s length divided by its diameter has a result a constant named PI; This value is known since ancient times by the Greeks and Egyptians, but only in current history this constant has been recognized as an irrational number. This study has as objective to explore the relationship of the circle by II elementary school students and extension of numerical sets from this constant. Making sense of this value by checking its regularity in all circles through practical experiments and also exploring the technological resources available in the school, making the students to follow the steps for determining of the numerical value and to participate in the construction and discovery process of new knowledge. The teaching sequence proposed was based on Engineering teaching as research methodology, conducting in the end a posteriori analysis which demonstrates that learning from manipulable objects, together with technological resources available provides to students with a greater assimilation of mathematical content, one becoming a remarkable experience for elementary school students and being an important tool which complements the lessons and makes them more participative. It is hoped that this work support math teachers to reflect the usage of manipulative materials, educational software and all available resources which provide greater assimilation and approach the student with the mathematical concepts.
Keywords: Círculo; Números irracionais; Valor de PI; Materiais manipulativos; Software educacional; Circle; Value of PI; Irrational; Manipulative materials; Educational software; CIENCIAS EXATAS E DA TERRA::MATEMATICA